Improvement in neoantigen prediction via integration of RNA sequencing data for variant calling - Nguyen, Bui Que Tran; Tran, Thi Phuong Diem; Nguyen, Huu Thinh; Nguyen, Thanh Nhan; Pham, Thi Mong Quynh; Nguyen, Hoang Thien Phuc; Tran, Duc Huy; Nguyen, Vy; Tran, Thanh Sang; Pham, Truong-Vinh Ngoc; Le, Minh-Triet; Phan, Minh-Duy; et al. (Frontiers in Immunology, 2023)
Neoantigen-based immunotherapy has emerged as a promising strategy for improving the life expectancy of cancer patients. This therapeutic approach heavily relies on accurate identification of cancer mutations using DNA sequencing (DNAseq) data. However, current workflows tend to provide a large number of neoantigen candidates, of which only a limited number elicit efficient and immunogenic T-cell responses suitable for downstream clinical evaluation. To overcome this limitation and increase the number of high-quality immunogenic neoantigens, we propose integrating RNA sequencing (RNAseq) data into the mutation identification step in the neoantigen prediction workflow. In this study, we characterize the mutation profiles identified from DNAseq and/or RNAseq data in tumor tissues of 25 patients with colorectal cancer (CRC). We detected only 22.4% of variants shared between the two methods. In contrast, RNAseq-derived variants displayed unique features of affinity and immunogenicity. We further established that neoantigen candidates identified by RNAseq data significantly increased the number of highly immunogenic neoantigens (confirmed by ELISpot) that would otherwise be overlooked if relying solely on DNAseq data. In conclusion, this integrative approach holds great potential for improving the selection of neoantigens for personalized cancer immunotherapy, ultimately leading to enhanced treatment outcomes and improved survival rates for cancer patients.